Variation in Sensitivity of Different Grapevine Genotypes to Erysiphe necator Growing under Unfavourable Climatic Conditions - Boso, S.; Gago, P.; Santiago, J.L.; Martínez, M.C. (South African Journal of Enology and Viticulture, 2018)
This paper reports the susceptibility to powdery mildew of 41 grapevine genotypes growing in the north and northwest of Spain over a three-year period. Although the humid climate of these vine-growing areas is not particularly favourable to the development of this disease, serious damages appears in some years when dry weather alternates with times of some rain. All the examined genotypes belonged to the collection of the Misión Biológica de Galicia (CSIC) (Pontevedra, Galicia, Spain). The incidence and severity of powdery mildew were determined on leaves three weeks after the onset of flowering and on clusters at harvest. The values for both variables were smaller than those recorded for other fungal diseases, although great differences in susceptibility between the different genotypes were observed. The most susceptible was Castañal (recently included in the Spanish Registry of Commercial Varieties), a genotype native to the O Rosal subzone of the Rias Baixas denomination of origin area. The present results could help viticulturalists grow different grapevine genotypes more successfully in regions with climatic conditions similar to those where the study was undertaken.